Broadcast news & writing stylebook - Papper, Robert A. (N. York Routledge, 2021)
"Broadcast News and Writing Stylebook is the go-to resource for writing broadcast news, offering readers the know-how to write excellent stories for television, radio, podcasts, and online media. Through clear and concise chapters, this text provides the fundamental rules of broadcast news writing, teaching readers how to craft stories on government, crime, weather, education, health, sports, and more. It covers the necessary mechanics news writers needs to know, including the nuances of reporting, grammar, style, and usage. This new seventh edition is updated with the latest on how stations incorporate online and social media strategies, as well as insights into the directions local news is headed. Author Robert Papper has over a quarter century of broadcast news and industry research experience and once again updates this vital text with the information necessary for being a successful news writer today. Also available for this edition is an Instructor's Guide, found on the book's webpage. Whether you're a student seeking to learn the mechanics of successful broadcast news writing or a working professional looking for a definitive reference for your desk, Broadcast News and Writing Stylebook offers a comprehensive guide to writing for television, audio, and beyond"--
Includes bibliographical references and index.
Keywords: Broadcast journalism -- Authorship; Journalism -- Style manuals; Report writing